Mine Mill Fights Back: Mine Mill/CAW Local 598 Strike 2000-2001, Sudbury - Beck, Kaili; Kinsman, Gary; Steedman, Mercedes; Suschnigg, Peter; Bowes, Chris (Mine Mill / CAW Local 598, 2005)
Illustrated history of the 2000-2001 strike of the Mine Mill/Canadian Auto Workers Local 598 strike against Falconbridge in Sudbury, Ont. Published in collaboration with Laurentian University's Labour and Trade Union Studies' Program.
Keywords: History; Labor Unions; Mineral industries; Miners; Social aspects; Strikes and lockouts

Structure and Operation of the Steelworkers - Brasch, Hans (Journal Printers, 2005)
Abundantly illustrated update of "A Miner's Chronicle" from 1998 to 2004, that emphasizes union-related activities and events. Also includes a list of mining fatalities.
Keywords: History; Labor Unions; Miners; Sudbury; Ont.; United Steelworkers of America. Local 6500

From UI to EI: Waging War on the Welfare State - Campeau, Georges; Howard, Richard (UBC Press, 2005)
Established in 1940 in response to the Great Depression, the original goal of Canada’s system of unemployment insurance was to ensure the protection of income to the unemployed. Joblessness was viewed as a social problem and the jobless as its unfortunate victims. If governments could not create the right conditions for full employment, they were obligated to compensate people who could not find work. While unemployment insurance expanded over several decades to the benefit of the rights of the unemployed, the mid-1970s saw the first stirrings of a counterattack as the federal government’s Keynesian strategy came under siege. Neo-liberalists denounced unemployment insurance and other aspects of the welfare state as inflationary and unproductive. Employment was increasingly thought to be a personal responsibility and the handling of the unemployed was to reflect a free-market approach. This regressive movement culminated in the 1990s counter-reforms, heralding a major policy shift. The number of unemployed with access to benefits was halved during that time. From UI to EI examines the history of Canada’s unemployment insurance system and the rights it grants to the unemployed. The development of the system, its legislation, and related jurisprudence are viewed through a historical perspective that accounts for the social, political, and economic context. Campeau critically examines the system with emphasis upon its more recent transformations. This book will interest professors and students of law, political science, and social work, and anyone concerned about the right of the unemployed to adequate protection. –Publisher's description. Contents: Why UI? – The British Act of 1911 – Developing a Canadian system – The UI Act of 1940 – UI expansion, 1940-75 – Vision under siege, 1975-88 – Rights enshrined in case law, 1940-90 – The system hijacked, 1989-96 – Onward to EI – Case law in the neoliberal riptide of the 1990s. Translation of: De l'assurance-chômage à l'assurance-emploi.
Keywords: History; Law and legislation; Unemployment insurance

Self-Employed Workers Organize: Law, Policy, and Unions - Cranford, Cynthia; Fudge, Judy; Tucker, Eric; Vosko, Leah F. (McGill-Queen's University Press, 2005)
Over a million self-employed Canadians work every day but many of them are not entitled to the basic labour protections and rights such as minimum wages, maternity and parental leaves and benefits, pay equity, a safe and healthy working environment, and access to collective bargaining. The authors of "Self-Employed Workers Organize" offer a multi-disciplinary examination of the legal, political, and social realities that both limit collective action by self-employed workers and create huge impediments for unions attempting to organize them. Through case studies of newspaper carriers, rural route mail couriers, personal care workers, and freelance editors - four groups who have led pioneering efforts to organize - the authors provide a window into the ways political and economic conditions interact with class, ethnicity, and gender to shape the meaning and strategies of working men and women and show how these strategies have changed over time. They argue that the experiences of these workers demonstrate a pressing need to expand collective bargaining rights to include them. –Publisher's description
Book available at Internet Archive to readers with print disabilities: https://archive.org/details/selfemployedwork0000unse
Keywords: Case studies; Labor unions; Legal status; laws; etc.; Organizing; Self-employed

Discounted Labour: Women Workers in Canada, 1870-1939 - Frager, Ruth A.; Patrias, Carmela (University of Toronto Press, 2005)
The years between 1870 and 1939 were a crucial period in the growth of industrial capitalism in Canada, as well as a time when many women joined the paid workforce. Yet despite the increase in employment, women faced a difficult struggle in gaining fair remuneration for their work and in gaining access to better jobs. Discounted Labour analyses the historical roots of women's persistent inequality in the paid labour force. Ruth A. Frager and Carmela K. Patrias analyse how and why women became confined to low-wage jobs, why their work was deemed less valuable than men's work, why many women lacked training, job experience, and union membership, and under what circumstances women resisted their subordination. Distinctive earning discrepancies and employment patterns have always characterized women's place in the workforce whether they have been in low-status, unskilled jobs, or in higher positions. For this reason, Frager and Patrias focus not only on women wage-earners but on women as salaried workers as well. They also analyze the divisions among women, examining how class and ethnic or racial differences have intersected with those of gender. Discounted Labour is an essential new work for anyone interested in the historical struggle for gender equality in Canada. –Publisher's description
Book available at Internet Archive to readers with print disabilities: https://archive.org/details/discountedlabour0000frag
Keywords: 19th century; 20th century; Canada; Employment; History; Sexual division of labor; Women

Bora Laskin: Bringing Law to Life - Girard, Philip (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2005)
In the history of twentieth-century Canadian law, Bora Laskin (1912-1984) is by all accounts one of its most important figures. Born in northern Ontario to Russian-Jewish immigrant parents, Laskin became a prominent human rights activist, university professor, and labour arbitrator before embarking on his 'accidental career' as a judge on the Ontario Court of Appeal, a member of the Supreme Court of Canada, and Chief Justice of Canada. Throughout his entire professional life, he used the law to make Canada a better place for workers, racial and ethnic minorities, and the disadvantaged. As a judge, he sought to make the judiciary more responsive to changing expectations in regard to justice and fundamental rights." "In this biography, Philip Girard chronicles the life of a man who fought corporate capital, university boards, the Law Society of Upper Canada, and his own judicial colleagues in an effort to modernize institutions and reshape Canadian law. Girard draws on a wealth of previously untapped archival sources to provide, in vivid detail, a critical assessment of the contributions of a dynamic man on an important mission. –Book cover description
OCLC: 60416363
Keywords: Biographies; Biographies; memoirs and correspondance; Canada; Canada. Cour suprême Biographies; Canada. Supreme Court; Canada. Supreme Court Biography; Canada. Supreme Court History; Electronic books; Judges; Judges Canada Biography; Juges Canada Biographies; Laskin; Bora; Supreme court

Ontario Public Service Employment & Labour Law - Hadwen, Timothy; Eady, Don; Marvy, Leonard; Strang, David (Irwin Law, 2005)
This book deals with the Crown Employees Collective Bargaining Act and the Public Service Act, the statutes that primarily govern unionized and non-unionized employment and labour relations in the Ontario Public Service and Crown Agencies. The book provides a full review of all sections, and all judicial and arbitral consideration, of both acts. It also discusses the unique treatment of the Crown and its employees in the Public Sector Labour Relations Transition Act and the Employment Standards Act.
Keywords: Civil service; Collective labor agreements; Employee-management relations in government; Government employees; Law and legislation; Ontario

The Workers' Festival: A History of Labour Day in Canada - Heron, Craig; Penfold, Steve (University of Toronto Press, 2005)
For most Canadians today, Labour Day is the last gasp of summer fun: the final long weekend before returning to the everyday routine of work or school. But over its century-long history, there was much more to the September holiday than just having a day off. In The Workers' Festival, Craig Heron and Steve Penfold examine the complicated history of Labour Day from its origins as a spectacle of skilled workers in the 1880s through its declaration as a national statutory holiday in 1894 to its reinvention through the twentieth century. The holiday's inventors hoped to blend labour solidarity, community celebration, and increased leisure time by organizing parades, picnics, speeches, and other forms of respectable leisure. As the holiday has evolved, so too have the rituals, with trade unionists embracing new forms of parading, negotiating, and bargaining, and other social groups re-shaping it and making it their own. Heron and Penfold also examine how Labour Day's monopoly as the workers' holiday has been challenged since its founding, with alternative festivals arising such as May Day and International Women's Day. The Workers' Festival ranges widely into many key themes of labour history - union politics and rivalries, radical movements, religion (Catholic and Protestant), race and gender, and consumerism/leisure - as well as cultural history - public celebration/urban procession, urban space and communication, and popular culture. From St. John's to Victoria, the authors follow the century-long development of the holiday in all its varied forms. –Publisher's description
Available at Internet Archive to readers with print disabilities: https://archive.org/details/illustratedhisto0000unse_q6n8/mode/2up

Madeleine Parent: Activist - Lévesque, Andrée (Sumach Press, 2005)
"[B]rings together some of the papers presented at the conference, "Madeleine Parent, ses lutes et ses engagements /Madeleine Parent and her struggles," held in March 2001 at McGill University under the auspices of the Quebec Studies Programme and the McGill Centre for Research and Teaching on Women." – Editor. Translation of: Madeleine Parent, militante (2003). Contents: Portfolio of photographs – Introduction: setting the stage; Student life at McGill, 1936-1940 / Andrée Lévesque – Textile strikes in Quebec: 1946, 1947, 1952 / Denyse Baillargeon – Carrying on the struggle in Ontario, 1952-1973 / John Lang – The Atlantic connection / John St-Amand – The women's movement in Canada: setting the agenda / Lynn Kaye & Lynn Mcdonald – The importance of being Madeline: how an inactivist won the heart of Quebec's immigrant and minority women – A tribute to a valiant lady / Françoise David – Madeleine Parent: an unfailing ally of native women / Michèle Rouleau – An iron will and a string of pearls / Rick Salutin – A friend, a role model / Monique Simard.
Keywords: Feminism; History; Parent; Madeleine; 1918-2012; Social conditions; Syndicalism; Women political activists

Global Game, Local Arena: Restructuring in Corner Brook, Newfoundland - Norcliffe, Glen (Memorial University Press, Institute of Social and Economic Research, 2005)
In Global Game, Local Arena, geographer Glen Norcliffe explores how powerful forces of global economic integration have played out in Corner Brook and interprets the town's creation as a company town in the colonial era, its slow transformation into a public municipality, and the phase of vigorous restructuring launched in 1984 to raise the paper mill's performance in response to increased global competition. Restructuring introduced lean production, and in turn this impacted on workers' families, and on the larger community. Through extensive interviews with former and present mill workers and their families, and by examining written records — newspaper accounts, legislative acts, earlier published sources — the author sheds valuable light on how the process of globalization has played out in one small but typical local arena. Since 1984 Corner Brook has experienced large-scale out-migration of younger adults, and a rapid aging of the population. Community resistance to this process has been mostly subtle, taking the form of a reconnection to the population's local roots in outports and the woods. –Publisher's description
OCLC: 836228196

Ma vie de syndicaliste - Parrot, Jean-Claude (Boréal, 2005)
Pendant quinze ans, Jean-Claude Parrot a occupé le poste de président du Syndicat des travailleurs et travailleuses des postes, et pendant plus de dix-huit ans, il en a été le négociateur en chef. Au cours de toutes ces années, le leadership de Jean-Claude Parrot a fait de ce syndicat un des plus militants et des plus démocratiques au Canada. Quand Pierre Elliott Trudeau a décidé de transformer le service postal en société de la Couronne, c’est Parrot qui était à la barre. C’est lui également qui a supervisé la fusion des divers syndicats des postiers en un seul grand syndicat. Jean-Claude Parrot raconte ici son histoire, mais en même temps celle de la formation d’une grande union syndicale. Il raconte également comment la démocratie syndicale s’est construite – comment les membres de la base ont pu s’imposer dans tout le mécanisme de prise de décisions. Ce livre nous permet de suivre la carrière de l’un des plus grands dirigeants syndicaux du Canada, de le voir engagé dans son combat pour donner une voix aux travailleurs. Dans ce combat, Parrot a souvent placé son engagement syndical avant sa vie privée, et il a préféré faire de la prison plutôt que de sacrifier ses principes. À travers le récit de Jean-Claude Parrot, nous voyons la démocratie en marche, nous voyons le combat d’un homme pour défendre la cause des travailleurs et des syndicats. Traduit de l'anglais (Canada) par Claire Laberge –Résumé de l'éditeur
OCLC: 500202546

My Union, My Life: Jean-Claude Parrot and the Canadian Union of Postal Workers - Parrot, Jean-Claude (Fernwood, 2005)
Jean-Claude Parrot was National President of the Canadian Union of Postal Workers for fifteen years and its chief negotiator for eighteen. During that time he provided the leadership which built what became Canada’s most militant and democratic union. When Pierre Trudeau decided to make the post office a crown corporation Parrot was there to guide the transition. He was also there to oversee the merger of the various postal unions into “one union for all.” As well as Jean-Claude Parrot’s story, this is also the story of the formation of a union. It is a story of how union democracy was built–of how the grassroots union membership became an integral part of decision making in the union. In the pages of this book you will follow the life of one of Canada’s greatest union leaders as he fought to give the workers a voice. In the course of the struggle Parrot often put his union work and commitments before his own personal life and spent time in prison rather than sacrifice his principles and the cause of the workers in the union. Through Parrot’s recounting of these years we learn about how the struggle was waged, how democracy was built and how a union leadership worked tirelessly in the service of the union membership. –Publisher's description
https://fernwoodpublishing.ca/book/my-union-my-life
Keywords: Biography; Canadian Union of Postal Workers; Officials and employees; Parrot; Jean-Claude; Postal service

What Do They Call a Fisherman?: Men, Gender, and Restructuring in the Newfoundland Fishery - Power, Nicole Gerarda (Memorial University Press, Institute of Social and Economic Research, 2005)
Newfoundland fisheries have been transformed from an industry once dominated by petty commodity production and merchant-fisher relations to one dominated by private enterprise and corporate capitalism. State efforts to enclose the fisheries through boat quotas and to limit participation through a core classification system demonstrate a shift in values. Science-based regulation, in which the estimates of fisheries scientists were overly optimistic, led to the collapse of the cod fishery. The recent turn to a fishery based on classical economics, emphasizing professionalization, has left inshore fishers caught between two value systems. The traditional view valorizes hard work and local knowledge about the fishing environment; the modern view embraces technology, rationalization and professionalization. In [this book] Nicole Power examines, through a feminist lens, how this tension between two views — between a way of life and a way to make a living — and how these changes have affected men (and women) in the Bonavista and Trinity Bays inshore fishery. Has a "crisis of fish" and the loss or diminution of livelihood led to a "crisis of masculinity"? Through extensive interviews with fishers and fish-plant workers, the author discovers that men have responded to restructuring in complex ways that are mediated, enabled and constrained by their class and gender positions, and by maritime cultural values and practices. –Publisher's description
OCLC: 835553416

The Tyranny of Work: Alienation and the Labour Process - Rinehart, James W. (Nelson, 2005)
[E]xamines the institution of work from the perspective of alienated labour, a perspective that many conventional approaches to the subject have ignored or misrepresented. Completely updated to reflect current trends in the labour force and research in the field of labour studies, The Tyranny of Work begins with a thorough discussion of work as a social problem and the sources of alienation. The book then examines the development of industrial capitalism in Canada, the white-collar and blue-collar worlds, and, finally, solutions to the problem of alienated labour. All statistics and data have been updated to reflect the most current research. Information from the 2001 Census has been integrated throughout the text. The Tyranny of Work examines the institution of work from the perspective of alienated labour, a perspective that many conventional approaches to the subject have ignored or misrepresented. –Publisher's description
Keywords: Alienation (Social psychology); Labor; Working class

Labour in the Laboratory: Medical Laboratory Workers in the Maritimes, 1900-1950 - Twohig, Peter (McGill-Queen's University Press, 2005)
Medical laboratory technology is currently the third largest health profession in Canada but those who work in it remain largely invisible, both to the public and in the literature. In Labour in the Laboratory Peter Twohig examines the origins of the laboratory workforce in the Maritime provinces and rethinks the broader history of the twentieth-century Canadian hospital. –Publisher's description.
Book available at Internet Archive to people with print disabilities: https://archive.org/details/labourinlaborato0000twoh
Keywords: 20th century; Biomedical technology; History; Hospital laboratories; Maritime Provinces; Medical Laboratory Personnel; Medical technologists

On the Side of the People: A History of Labour in Saskatchewan - Warren, Jim W.; Carlisle, Kathleen (Coteau Books, 2005)
A comprehensive history of working people in Saskatchewan, from the mid-1800s to the present, in a handsome coffee-table format, including numerous historical photos of the personalities and events that bring it to life. This book is created for the working people that it celebrates. In a plain-spoken and engaging narrative style, it captures the events and the personalities that shaped the working people of Saskatchewan, and the life of the province that those workers built. Jim Warren tells the fascinating tale of jobs, working conditions, and the attempts to effect meaningful changes in the condition of workers' lives. Starting with the Fur Trade period, and moving through the arrival of the railroad brotherhoods, the emergence of the craft unions, two world wars, modernization, and into the present age, Working in Saskatchewan shows the evolution of the work force, and the relationship between that work force and both private and public sector employers. The book wraps up with a short chapter on the imagined future of labour in the province, in the voices of a series of speakers ranging from former Premier Allan Blakeney to ordinary workers on the floor of a recent SFL convention. Working in Saskatchewan also includes a number of features that will make it even more useful for private study or school work. Two comprehensive indexes detail the chief characters who played a role in the development of the labour movement, and a list of events and important topics. A series of informational appendices present statistical information relating to the Saskatchewan labour force - size of the organized and unorganized labour force, number of women in the work force, etc. There will also be a helpful glossary of the acronyms and abbreviations that characterize written or oral discussions about labour, and a "genealogy of labour" which charts the rise and growth of certain unions and their transformation into, or absorption by, others. –Publisher's description
OCLC: 62087199
Keywords: History; Labor movement; Labor movement Saskatchewan History; Labor unions; Labor unions Saskatchewan History; Mouvement ouvrier Saskatchewan Histoire; Saskatchewan; Saskatchewan Conditions sociales; Saskatchewan Social conditions; Social conditions; Syndicats Saskatchewan Histoire; Travailleurs Saskatchewan Histoire; Working class; Working class Saskatchewan History